2013
DOI: 10.1097/ico.0b013e3182910036
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Risk of 100% Autologous Serum Eye Drops in Management of Ocular Surface Diseases

Abstract: Although no ocular surface infection was observed, the patients under 100% autologous serum eye drops therapy should be closely monitored for clinical evidence of fungal and bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Preoperative topical and systemic therapy for ocular GVHD and concurrent systemic GVHD are shown in Table 4. Treatment with topical autologous serum was discontinued three days prior and until one week after surgery since it is rich in protein and growth factors, and hence may increase the risk of microbial colonization and infection in the setting of intraocular surgery [14,15]. Scleral contact lenses were removed immediately before intraocular lens calculation to ensure an even ocular surface and accurate biometry, to subsequently resume their use until the day of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative topical and systemic therapy for ocular GVHD and concurrent systemic GVHD are shown in Table 4. Treatment with topical autologous serum was discontinued three days prior and until one week after surgery since it is rich in protein and growth factors, and hence may increase the risk of microbial colonization and infection in the setting of intraocular surgery [14,15]. Scleral contact lenses were removed immediately before intraocular lens calculation to ensure an even ocular surface and accurate biometry, to subsequently resume their use until the day of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is no evidence of systemic effects that might limit the use of platelet derivatives if we exclude the possible risk of infections [35][36]; indeed, few randomized controlled trials reported adverse events although without a proven causal relation with the application of these…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…In the absence of pathogen inactivation treatment, the use of autologous platelet derivatives avoids the ethical and legal implications of exposing the patient to the viral risks of allogenic blood components [34], especially in countries with high infectious rates and with limited donor screenings and donation tests [35]. In contrast, autologous products carry only the risk of infection related to contamination during collection and handling [36]. Furthermore, autologous products may be more acceptable to patients.…”
Section: Collection and Preparationmentioning
confidence: 97%
“…Most publications report the use of open manufacturing systems to produce serum eye drops, often under semisterile conditions, leading to a higher risk of contamination and ultimately infection 16 17. In addition, a recent survey among ASED users demonstrated that while user convenience was similar for both bottled products (manufactured open under sterile conditions) and a closed manufacturing system (manufactured using a sealed system), patients nonetheless prefer bottled products due to reduced costs 18.…”
Section: Introductionmentioning
confidence: 99%